2020
DOI: 10.1136/annrheumdis-2020-216988
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes and treatment responses, including work productivity, among people with axial spondyloarthritis living in urban and rural areas: a mixed-methods study within a national register

Abstract: ObjectiveTo examine differences in clinical and patient-reported outcomes, including work, in individuals with axial spondyloarthritis (axSpA) living in rural and urban settings.MethodsUsing a sequential, explanatory mixed-method design, data from the British Society for Rheumatology Biologics Register for Ankylosing Spondylitis were used to (1) characterise participants with axSpA living in rural and urban areas and (b) assess any differences in outcome after commencement of biologic therapy (phase 1). Semist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 24 publications
(34 citation statements)
references
References 39 publications
0
30
0
Order By: Relevance
“…The ability to work has a positive impact on psychosocial health; this is, however, impaired by musculoskeletal disorders such as axSpA. 53 Up to 30% of patients with axSpA are affected by work disability, and patients with axSpA are three times more likely to withdraw from work compared with those without axSpA, particularly from physically demanding jobs. 53 Presenteeism (productivity loss due to ill health) and work impairment are often experienced by patients with axSpA, which in turn leads to absenteeism (being absent from work due to ill health) and job loss.…”
Section: Secukinumabmentioning
confidence: 99%
See 2 more Smart Citations
“…The ability to work has a positive impact on psychosocial health; this is, however, impaired by musculoskeletal disorders such as axSpA. 53 Up to 30% of patients with axSpA are affected by work disability, and patients with axSpA are three times more likely to withdraw from work compared with those without axSpA, particularly from physically demanding jobs. 53 Presenteeism (productivity loss due to ill health) and work impairment are often experienced by patients with axSpA, which in turn leads to absenteeism (being absent from work due to ill health) and job loss.…”
Section: Secukinumabmentioning
confidence: 99%
“… 53 Up to 30% of patients with axSpA are affected by work disability, and patients with axSpA are three times more likely to withdraw from work compared with those without axSpA, particularly from physically demanding jobs. 53 Presenteeism (productivity loss due to ill health) and work impairment are often experienced by patients with axSpA, which in turn leads to absenteeism (being absent from work due to ill health) and job loss. 53 Work Productivity and Activity Impairment (WPAI) is an instrument commonly used to measure work productivity in patients and includes questions to assess absenteeism, presenteeism and overall work productivity impairment.…”
Section: Secukinumabmentioning
confidence: 99%
See 1 more Smart Citation
“…A higher risk of MACE in rural AS patients has not been sufficiently reported in the current English literature. Rural AS patients were found to be older, have labour-intensive jobs, and experienced presenteeism and impaired work productivity [ 24 ]. The abovementioned characteristics might make them more prone to MACE development compared with their urban counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, 9 out of 10 workers in one national survey reported that they got at least as much, if not more, work done at home as in the office, with almost three quarters of employees saying that they wanted to adopt hybrid working arrangements in the future. 25 For people with MSK conditions, we have already shown that commuting to work, and driving, can be a significant challenge for people with inflammatory arthritis, 7 26 and these findings suggest that, for many, reduced need for commuting was beneficial.…”
Section: Discussionmentioning
confidence: 99%